3D Printing of Strontium Silicate Microcylinder‐Containing Multicellular Biomaterial Inks for Vascularized Skin Regeneration. Issue 16 (8th May 2021) - Ma, Jingge; Qin, Chen; Wu, Jinfu; Zhang, Hongjian; Zhuang, Hui; Zhang, Meng; Zhang, Zhaowenbin; Ma, Lingling; Wang, Xin; Ma, Bing; Chang, Jiang; Wu, Chengtie
Abstract: The reconstruction of dermal blood vessels is essential for skin regeneration process. However, the lack of vascular structure, insufficient angiogenesis induction, and ineffective graft‐host anastomosis of the existing skin substitutes are major bottle‐necks for permanent skin replacement in tissue engineering. In this study, the uniform strontium silicate (SS) microcylinders are successfully synthesized and integrated into the biomaterial ink to serve as stable cell‐induced factors for angiogenesis, and then a functional skin substitute based on a vascularization‐induced biomimetic multicellular system is prepared via a "cell‐writing" bioprinting technology. With an unprecedented combination of vascularized skin‐mimicking structure and vascularization‐induced function, the SS‐containing multicellular system exhibits outstanding angiogenic activity both in vitro and in vivo. As a result, the bioprinted skin substitutes significantly accelerate the healing of both acute and chronic wounds by promoting the graft‐host integration and vascularized skin regeneration in three animal models. Therefore, the study provides a referable strategy to fabricate biomimetic multicellular constructs with angiogenesis‐induced function for regeneration of vascularized complex and hierarchical tissues. Abstract : The uniform strontium silicate microcylinders are prepared and integrated into the hydrogel as stable "growth factors". Then a vascularization‐induced biomimetic multicellular system is established via a "cell‐writing" bioprinting method to simulate the physiological structure of skin containing blood vessel network. The dual‐induced angiogenesis effect of the system greatly benefits the treatment of both acute and chronic wounds.